Comparison of Bottom Gillnet Catches with Different Mesh Sizes in the Waters of Sungai Jambat Village, Sadu District - Ardiansyah, Ardiansyah; Nelwida, Nelwida; Sulaksana, Indra; Alwi, Yun; Lisna, Lisna; Farizal, Farizal (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Sadu District is located in East Tanjung Jabung Regency and consists of 9 villages, one of which is Sungai Jambat Village which is characterized by turbid, wavy, muddy, and sandy waters. The majority of fishermen in Sungai Jambat Village use bottom gillnet fishing gear with a mesh size of 3.5 inches and 4 inches. The purpose of this study was to compare the catches of bottom gillnet with mesh sizes of 3.5 inches and 4 inches in the waters of Sungai Jambat Village. The method used in this research is the experimental fishing method. The data collected includes environmental parameters, catch per species (head), and number of catches (head), weight per species (kg), and the total weight of catch (kg). The data analysis used is the descriptive analysis of an independent sample t-test. The results showed that the 3.5-inch mesh treatment was significantly higher than the 4-inch mesh treatment (p<0.05) in terms of the number and weight of bottom gillnet catches. In the 3.5-inch mesh size, the catch was 3,067 individuals with a weight of 248.40 kg, and the number of catches in the 4-inch mesh size was 2,820 individuals with a weight of 234.60 kg. The highest number of catches was leaftail croaker found in a 3.5-inch mesh size of 1,393 individuals, and mantis shrimp was the heaviest catch in a 3.5-inch mesh size weighing 69 kg. Pomfret is the lowest catch in terms of quantity and weight. The conclusion of this study in terms of the number and weight of catches with a 3.5-inch mesh size is higher than the 4-inch mesh size.